Abnormalities in Lipid Profile Amongst Type 1 and Type 2 Diabetes in North Indian Population - Gupta, Vikas (International Journal of Scientific Research in Biological Sciences, 2019)
Diabetes mellitus is characterized by hyperglycemia resulting from defects in insulin secretion, insulin action, or both. Lipid abnormalities which can occur in diabetes mellitus can further complicate management of patients and is believed to play an important role in the pathogenesis of atherosclerosis. Keeping the above in view the present study aims to look for association between the lipid profile amongst diabetic patients and normal healthy controls in the Punjabi population. To meet the above objective blood samples were collected from a total of 100 diabetic subjects (20 type 1 and 80 type 2 diabetes) visiting the OPD and ward of department of medicine, in Civil Hospitals of Kapurthala, Jalandhar and Amritsar and 100 normal healthy controls matched for age and sex. Each patient was investigated for plasma glucose fasting (FPG), glycosylated hemoglobin (HbA1c), serum cholesterol (TC), serum triglyceride (TG), high density lipoproteins (HDL) low density lipoproteins (LDL) and very low density lipoproteins (VLDL). The mean serum cholesterol, triglycerides, LDL cholesterol, VLDL cholesterol and HDL cholesterol in diabetic subjects were 191.27 + 30.85 mg/dl, 159.11+ 37.11 mg/dl, 115.80 + 25.62 mg/dl, 31.48 + 7.68 mg/dl and 43.22 + 5.00 mg/dl while their levels in normal healthy individuals were 166.21 + 9.67 mg/dl, 123.69 + 15.87 mg/dl, 96.57 + 7.97 mg/dl, 24.78 + 3.15 mg/dl and 44.90 + 1.49 mg/dl respectively. The mean serum cholesterol, triglycerides, LDL cholesterol and VLDL cholesterol was significantly higher while serum HDL value was significantly lower in diabetic subjects as compared to non diabetic subjects. This study shows dyslipidemia among diabetic patients and proposes that the failure to recognize the presence of abnormal lipid profile may be a primary cause of poor management often encountered in some of the treated diabetics.